Aligning Technical and Vocational Curricula with Labor Market Needs to Foster Economic Growth in Afghanistan: An Empirical Study - Mazloum Yar, Fayaz Gul; Azimi, Basir Ahmad (Green Publisher Indonesia, 2025)
This study investigates how the design and implementation of technical and vocational education and training (TVET) curricula can be optimized to meet evolving labor market demands and thereby stimulate sustainable economic growth in Afghanistan. Employing a convergent mixed-methods approach, quantitative data were collected via a structured questionnaire administered to 312 TVET graduates and 48 industry employers across Kabul, Herat, and Kandahar. Reliability and validity of the instrument were confirmed through Cronbach’s alpha (α = 0.87) and expert panel review. Qualitative insights were obtained from 20 semi-structured interviews with curriculum developers, trainers, and policymakers, and analyzed using thematic content analysis. Quantitative results demonstrate a statistically significant gap between current curriculum competencies and employer-identified skill requirements (t(359) = 5.42, p < 0.001), particularly in digital literacy (mean difference = 1.26 on a 5-point scale) and soft skills (mean difference = 0.98). Qualitative findings reveal three primary themes: (1) outdated course content, (2) limited industry-academic collaboration, and (3) resource constraints. Based on these findings, we propose a framework for iterative curriculum updates, strengthened partnerships with private-sector stakeholders, and targeted professional development for TVET instructors. Implementing these recommendations is expected to enhance graduate employability by up to 30% and contribute an estimated USD 0.5 billion annually to Afghanistan’s GDP. This study provides evidence-based guidance for policymakers, educators, and international development agencies aiming to align TVET curricula with market realities in post-conflict economies